“The First White Mother in America” Guðríðr Þorbjarnardóttir, Popular History, Firsting, and White Feminism - Crocker, Christopher (Scandinavian-Canadian Studies / Études scandinaves au Canada, 2023)
This article takes Ásmundur Sveinsson’s statue "The First White Mother in America" as a starting point. With reference to this work, its several later casts, and three illustrative examples from recent popular history writing, the article demonstrates how popular representations of the statue's subject, Guðríðr Þorbjarnardóttir, frequently reinforce traditions rooted in racially exclusive historical standards and Indigenous erasure. While Guðríðr’s story offers a valuable counterpoint to male-dominated and often hyper-violent images of “Viking” history, writers and other popular history purveyors depicting her story also run the risk of simultaneously reinforcing settler-colonial and white supremacist ideals regardless of their individual motives.